ANALISIS FAKTOR-FAKTOR YANG MEMPENGARUHI PDRB DAN DISPARITAS PENDAPATAN DI PROVINSI JAWA TIMUR - Mulyani, Cici Sri; Sakti, Rachmad Kresna (Fakultas Ekonomi dan Bisnis Universitas Brawijaya, 2022)
This study was conducted to analyze the factors that influence GRDP and income disparities in East Java Province for the 2008-2019 period. The research method used in this study is a quantitative research method using panel data analysis and multivariant analysis and the software used is Eviews. The results showed that population density, Human Development Index, Regional Original Income had a positive and significant effect on GRDP, meanwhile the Open Unemployment Rate had no significant effect in a positive direction and Capital Expenditure had a significant and negative effect on GRDP, and GRDP had a significant effect. and negative on income disparity in East Java Province.